2006
DOI: 10.1007/s00381-006-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive assessment in epilepsy surgery of children

Abstract: We underline the importance of multicentric studies with standardized neuropsychological assessments in large series of young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 83 publications
5
27
1
1
Order By: Relevance
“…This reassuring finding is consistent with those of prior studies 24, 27, 5558 . Despite the overall group-level stability, some individuals demonstrated significant changes in FSIQ.…”
Section: Discussionsupporting
confidence: 92%
“…This reassuring finding is consistent with those of prior studies 24, 27, 5558 . Despite the overall group-level stability, some individuals demonstrated significant changes in FSIQ.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the etiology and location of epilepsy, as well as the surgical procedures, differ considerably between children and adults [16]. The neuropsychological assessment before and after surgery allows for the identification of developmental delay, stagnation or deterioration and for the identification of predictive factors of cognitive development [17]. Few studies have reported the long-term neuropsychological outcome after epilepsy surgery in children [4,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the recognized role of presurgical neuropsychological evaluation of children with pharmacoresistant epilepsy [4,22], there are many methodological limits to perform it in patients with posterior quadrant dysplasia, i.e., the young age of the patients which unfavourably combines with the discontinuity of infantile scales and psychometric tests. The examination of neurosensory functions, in particular visual and auditory functions, according to the most recent attitude [2,13], might help in this context to evaluate some early aspects of neurodevelopment in these patients.…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%
“…More perplexities exist regarding the use of extraoperative subdural EEG monitoring. The main reasons that have been cited in favor of avoiding it in posterior quadrantic epilepsy patients are the following: [1] the likelihood of a multilobar epileptogenic zone, rendering it difficult to perform an adequate covering of it with grids and electrodes; [2] the anticipation that subdural EEG monitoring would similarly show widespread, nonlocalized EEG abnormalities or fail to localize seizures due to spatial sampling issues; [3] the minimal risk from TPO surgery to determine language or motor deficits, given the nature of the lesions and the degree of preexisting developmental delays; [4] the greater likelihood of seizure freedom with a multilobar procedure than with a localized resection, prompted by a subdural EEG finding; and [5] the added risks, costs, and delays associated with a protocol including extraoperative subdural EEG recordings [20]. A more uniform consent relates to the use of intraoperative cortical mapping.…”
Section: The Role Of Intraoperative Electrocorticography and Intraopementioning
confidence: 99%